Knowledge and Awareness of Monkeypox Prevention: A Case Study in Timor Leste - Joaquim Pinto; Francisca Jesuina Bere da Costa; Joaquim Gregorio de Carvalho; Maximiano Oqui; Carlos Boavida Tilman (Universitas STRADA Indonesia, 2025)
Monkey Pox is a pandemic or global problem and an international concern because the disease occurs in the world's most endemic and spread rapidly. According to data published by the Center for Disease Control and Prevention (CDC) in February 2023, there were up to 85.802 cases of worldwide, including 32 cases that resulted in death. With a total of 30.193 cases, the United States of America emerged as the country with the highest number of cases based on epidemiological data. The countries in Southeast Asia most affected by are Australia (41 cases), New Zealand (2 cases), Singapore (6 cases), South Korea (2 cases), Thailand (25 cases), and Indonesia (1 case).